2017
DOI: 10.1016/j.neuropharm.2017.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological characterization of the new psychoactive substance methoxetamine

Abstract: a b s t r a c tThe use of new psychoactive substances (NPS) is steadily increasing. One commonly used NPS is methoxetamine (MXE), a ketamine analogue. Several adverse effects have been reported following MXE exposure, while only limited data are available on its neuropharmacological modes of action.We investigated the effects of MXE and ketamine on several endpoints using multiple in vitro models. These included rat primary cortical cells, human SH-SY5Y cells, human induced pluripotent stem cell (hiPSC)-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…As neuronal activity is inhibited at concentrations several magnitudes above inhibition of uptake via hDAT and hNET, the monoamine transporters are a more sensitive endpoint for the cathinones tested. While this is true for cathinones, we have previously shown that neuronal activity is a more sensitive endpoint for other drugs like methoxetamine (MXE) and hallucinogenic phenethylamines 2C-B and multiple NBOMes (Hondebrink et al, 2017;Zwartsen et al, 2017Zwartsen et al, , 2018. As neuronal activity reflects many neuropharmacological targets of interest, in contrast to single targets like monoamine transporters, these measurements can be very valuable in screening for neuropharmacological effects of NPS, especially when the mechanism of action is a priori unknown.…”
Section: Discussionmentioning
confidence: 99%
“…As neuronal activity is inhibited at concentrations several magnitudes above inhibition of uptake via hDAT and hNET, the monoamine transporters are a more sensitive endpoint for the cathinones tested. While this is true for cathinones, we have previously shown that neuronal activity is a more sensitive endpoint for other drugs like methoxetamine (MXE) and hallucinogenic phenethylamines 2C-B and multiple NBOMes (Hondebrink et al, 2017;Zwartsen et al, 2017Zwartsen et al, , 2018. As neuronal activity reflects many neuropharmacological targets of interest, in contrast to single targets like monoamine transporters, these measurements can be very valuable in screening for neuropharmacological effects of NPS, especially when the mechanism of action is a priori unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, MXE‐induced antinociceptive effects might involve different sites in the brain, including non‐NMDA glutamate receptors, and other (not glutamatergic) neurotransmission systems (Forman, ). Indeed, MXE displayed affinity for the 5‐HT transporter, the dopamine transporter and the noradrenaline transporter but not for σ receptors (Roth et al, ; Hondebrink et al, ), was found to significantly activate the mesolimbic dopaminergic system (Mutti et al, ) and to inhibit monoamine transporters more potently than ketamine (Hondebrink et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of chemical similarities, MXE has been hypothesized to induce ketamine‐like effects (Hofer et al, ) and to produce a rapid antidepressant action (Coppola and Mondola, ). Preclinical studies have recently started investigating its pharmacokinetics, behavioural effects and underlying brain mechanisms (Hajkova et al, ; Horsley et al, ; Hondebrink et al, ). In rats, MXE was reported to induce conditioned place preference and maintain intravenous self‐administration behaviour (Botanas et al, ) and to substitute for ketamine in a drug self‐administration substitution study (Mutti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Having said that, given the very large number of NPS (up to 4000 by some estimations, there is little chance of all of these drugs being looked at in detail. The best that we can realistically hope for is putting many of these drugs through some high throughput screens for receptor/transporter binding and high throughput toxicity assays . An alternative approach is in silico testingi.e.…”
Section: Discussionmentioning
confidence: 99%